Metallomic profile in non-cirrhotic hepatocellular carcinoma supports a phenomenon of metal metabolism adaptation in tumor cells - Cano L. (2021)
This study was funded by the French National Alliance for Life Sciences and Health (ENV201408); LC was a recipient of a doctoral fellowship from French National Research Institute for Sustainable Development (IRD) (EMHE-ARTS-2016-878573B); JPC was a recipient of a doctoral fellowship from the Peruvian National Council for Science and Technology (212-2015-FONDECYT); SB has received funding from the European Union’s Horizon 2020 Framework program under the Marie Sk?odowska-Curie Actions 823935 and from the Alliance pour les Sciences de la Vie et de la Santé (AVIESAN), ITMO Cancer ENV201408, and LC, ER, and SCZ have received funding from the World Bank Group and FONDECYT-CONCYTEC 016-2018-FONDECYT/BM. The authors are grateful to Karina Cancino, Danny Cordova (INEN Cancer Research Biobank), Patricia Leroyer (NUMECAN), Alain Fautrel, Marine Seffals, Gevorg Ghukasyan (H2P2 platform). They also thank Dr Anne Corlu for the critical reviewing of the manuscript.